Taking a Diversity, Equity, Inclusion & Accessibility Lens to Engineering Librarian Job Postings: Recommendations from an Analysis of Postings from 2018 and 2019 (Journal of eScience Librarianship, 2022)
Objective: While diversity, equity, inclusion, and accessibility (DEIA) principles and practices have been incorporated into much of academic librarianship, there has been less focus on the job postings. Methods: In order to quantify ways in which DEIA is being integrated into job postings, we analyzed 48 job positions for engineering librarians posted in 2018 and 2019 via deductive thematic analysis, looking for trends in salary and qualifications related to education and academic or professional experience. Results: Of postings that listed a quantitative salary value, salary ranged from $45,000 to $81,606; the median was $60,750. However, only 33% (n = 16) of positions listed a quantitative salary value. For educational qualifications, we found that 98% of job postings (n = 47) listed a Master’s in Library and Information Science (MLIS) as a required qualification; however, 34% of these postings (n = 16) would accept an equivalent degree in lieu of the MLIS. Additionally, 73% (n = 35) of positions sought candidates with an MLIS and another degree; 91% of these positions (n = 32) wanted the additional degree to be in a science, technology, engineering, and mathematics discipline. For academic or professional experience, 56% of positions (n = 27) sought candidates with previous academic library experience. Conclusions: Using this data, we provide actionable recommendations on how to incorporate DEIA principles into any academic librarian job posting. Our study provides quantitative data and evidence-based recommendations that can be used to make DEIA an integral part of the job postings in academic librarianship.